Why Living Kidney Donor Candidates Are Turned Down? A Single-Center Cohort Study - Altheaby, Abdulrahman (Cureus, 2020)
Introduction Living donor kidney transplantation is the best replacement therapy for patients with end-stage renal disease. It offers more benefits than deceased donor transplantation. However, living kidney donors (LKDs) undergo an extensive evaluation to ensure their suitability for donation, and this can result in rejection of many potential donors. Aim The aim of this study was to recognize the reasons for declining LKDs in our Organ Transplant Center at King Abdulaziz Medical City. Settings and Design This was a retrospective study to determine the various reasons to reject an LKD at the Organ Transplant Center. Methods and Material All the LKDs from January 2016 to December 2019 were included. Declined donors were reviewed and data were obtained from the electronic database and transplant nephrology shared files. Statistical analysis We performed data analysis using SPSS version 24.0 (IBM Corp., Armonk, NY, USA). Data for continuous variables were presented as mean ± standard deviation and were compared using t-test. Categorical variables were presented as frequencies and percentages; chi-square test was used to test for main association and then Bonferroni adjustment was used for post-hoc testing. Statistical significance was considered if a two-tailed p-value of <0.05 was achieved. Results A total of 410 potential LKDs were evaluated, of whom 241 (58.8%) successfully underwent donor nephrectomy and 169 (41.2%) were unable to proceed for kidney donation. The most common reasons for rejection of LKDs were medical (47.9%) followed by immunological reasons mainly blood group incompatibility (19.5%). Other reasons were donor withdrawal (15.4%), recipient-related reasons (7.1%), surgically unfit to proceed for nephrectomy (4.7%), or psychological reasons (2.3%). Conclusions A significant proportion of potential LKDs did not complete the kidney donation process due to medical, immunological, and surgical reasons. In addition, a proportion of LKDs decided to withdraw at some point during the evaluation process. Investing in donors’ educational programs and implementing a standardized evaluation process are essential to increase LKDs pool.